2020
DOI: 10.1136/jclinpath-2020-206468
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic characteristics of HER2-positive metaplastic squamous cell carcinoma of the breast

Abstract: AimsThe aim of this study was to analyse the clinicopathological features and prognosis of human epidermal growth factor receptor-2 (HER2)-positive metaplastic squamous cell carcinoma (MSCC).MethodsFifty-eight patients with MSCC of the breast who were classified into 45 triple-negative and 13 HER2-positive subgroups diagnosed at the West China Hospital, Sichuan University, from 2004 to 2018, were enrolled. Clinicopathological features were collected and compared between HER2-positive MSCC, triple-negative MSCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Shui et al [ 15 ] reported that 3 of 30 cases of SCC (10%) were HER2 positive. Lei et al [ 16 ] reported that 13 of 58 cases of metaplastic SCC (22%) were HER2 positive. Additionally, because few clinicopathologic and therapeutic studies have examined HER2-positive SCC because of the rarity of the disease, the effect of neoadjuvant chemotherapy is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shui et al [ 15 ] reported that 3 of 30 cases of SCC (10%) were HER2 positive. Lei et al [ 16 ] reported that 13 of 58 cases of metaplastic SCC (22%) were HER2 positive. Additionally, because few clinicopathologic and therapeutic studies have examined HER2-positive SCC because of the rarity of the disease, the effect of neoadjuvant chemotherapy is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…HER2-positive breast cancer is rather unusual in SCC, and all available data regarding HER2-positive SCC of the breast were generated by case reports and small retrospective studies [1,[12][13][14][15][16], and the clinicopathologic features of this rare subtype of SCC have not been described in detail. In this study, we reported a case of HER2-positive SCC of the breast, an extremely rare breast cancer, which exhibited a pathological complete response to neoadjuvant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Conversely, HER2-positive metaplastic squamous cell carcinomas were recently demonstrated to have a poorer prognosis than the TN metaplastic squamous variants. 4 MpBC fit into the claudin-low and/or basal breast cancer intrinsic subtypes, 5 , 6 although whether or not claudin low represents an intrinsic subtype or phenotype has recently come into question. 7 A recent large meta-analysis reported that approximately three quarters of all MpBC stain positively for pan-cytokeratin biomarkers (AE1/3, MNF116) and basal cytokeratin biomarkers (34βE12, CK5/6, CK14 and CK17).…”
Section: Current Histopathological Classificationmentioning
confidence: 99%
“…Metaplastic squamous cell carcinoma of the breast (MSCCB) is a rare tumor that exists as one of the subgroups of metaplastic breast carcinoma, which accounts for less than 0.1% of all breast carcinomas (1). Since MSCCB is a very invasive tumor, its prognosis is poor (2). Besides, the cause and underlying mechanism of MSCCB remain unclear as a result of few clinical case reports and a lack of standard treatment guidelines.…”
Section: Introductionmentioning
confidence: 99%